Ultrasound indicates imbalance of superficial posterior cervical muscles: a sign of cervical degenerative instability - Chen, Guodong; Chen, Yaolong; Wang, Xin; Shi, Rui (BMC musculoskeletal disorders, 2025)
This study aimed to explore the association between changes in elasticity and thickness of the superficial posterior cervical muscles and cervical degenerative instability (CDS). CDS is primarily managed non-surgically, including manual and traction therapies. Thus, a diagnostic method to guide targeted non-surgical interventions is clinically valuable. A retrospective analysis was conducted on 20 CDS patients at Gansu Provincial Hospital of Traditional Chinese Medicine from October 2024 to March 2025. Ultrasound scans of the superficial posterior cervical muscles and X-rays (neutral, flexion, and extension views) were analyzed to evaluate muscle elasticity, thickness, and CDS characteristics. Among 20 CDS patients (mean age: 42.7 years; 55% female), cervical instability was most prevalent at C4-5 (50%, 10/20), followed by C5-6 (25%, 5/20), C3-4 (15%, 3/20), and C2-3 (10%, 2/20). At C4-5, trapezius imbalance was observed in 100% (10/10), splenius capitis in 70% (7/10), and levator scapulae in 50% (5/10). At C5-6, splenius capitis and levator scapulae imbalances were present in 100% (5/5), while trapezius imbalance occurred in 80% (4/5). Imbalance in the superficial posterior cervical muscles is associated with CDS. Ultrasound enables the detection of specific imbalanced muscles, providing guidance for CDS to deliver targeted non-surgical therapies including manual manipulation and traction. Additionally, with no radiation risks, ultrasound allows safe examination for special populations such as pregnant women. Therefore, ultrasound elastography of the superficial posterior cervical muscles is justified as a novel auxiliary diagnostic modality for cervical instability.